Research on Train Impulse Suppression Technology Based on Electronic Switch Ground Automatic Passing Neutral Section Device - Fan YANG (机车电传动)
In view of the serious train impulse caused by the application of the power electronic switch automatic passing neutral section technology, a dynamic moment unloading and loading control strategy was proposed which was suitable for the very short-term network voltage interruption, to realize the train traction force maintaining during the power loss time to actively suppress the train impulse;The generation mechanism of inrush current of transformer under the condition of extremely short-time switching of different phase network voltage was revealed, and the active suppression strategy of inrush current suitable for different phase network voltage switching was put forward; an optimized phase-locked strategy was expounded based on the combination of fast single-phase phase-locked and traditional phase-locked loop with coordinate transformation, which could effectively solve the problems of abnormal train control and traction long recovery time under the condition of passing neutral section with electronic switch. In the main line test of Shenshuo railway, the simulation of full load train passing through the power electronic switch neutral section, which fully proved the correctness and effectiveness of the proposed control strategy.